Properties of AGN in NIR within the context of the Eigenvector 1. Issue Volume 15:Issue S359(2020) (March 2019) - dos Santos, D. Dias; Rodríguez-Ardila, A.; Marinello, M.
Abstract: We present a spectral atlas of 70 type-I AGN with the wavelength ranging 0.4–2.5 μ m. For 37 sources, this is the first report of NIR spectroscopy in literature. The sample was constructed to study narrow line Seyfert 1 and quasars, with a large range of line widths (800 km s −1 < FWHM < 4000 km s −1 ) and Fe II intensities (0.2 < R 4570 < 2.8). This work presents partial results of an ongoing project that has the objective of modeling the continuum emission and emission lines in order to derive the physics driven the Eigenvector 1 through a panchromatic spectral analysis, with emphasis on strong to super-strong Fe ii emitters. Our results show that hot dust near the sublimation temperature is necessary to explain the 1 μ m break of the power law component of the continuum. We estimated the hot dust mass and found a weak or absent correlation with the Fe II intensity. Moreover, we found that low ionisation ions are formed in an outer region of the BLR.